Light-absorbing impurities in snow cover across Northern Xinjiang, China - Zhong, Xinyue; Kang, Shichang; Zhang, Wei; Yang, Junhua; Li, Xiaofei; Zhang, Yulan; Liu, Yajun; Chen, Pengfei (Journal of Glaciology, 2019)
Light-absorbing impurities (LAIs, e.g. black carbon (BC), organic carbon (OC), mineral dust (MD)) deposited on snow cover reduce albedo and accelerate its melting. Northern Xinjiang (NX) is an arid and semi-arid inland region, where snowmelt leads to frequent floods that have been a serious threat to local ecological security. There is still a lack of quantitative assessments of the effects of LAIs on snowmelt in the region. This study investigates spatial variations of LAIs in snow and its effect on snow albedo, radiative forcing (RF) and snowmelt across NX. Results showed that concentrations of BC, OC (only water-insoluble OC), MD ranged from 32 to 8841 ng g(-1), 77 to 8568 ng g(-1) and 0.46 to 236 mu g g(-1) respectively. Weather Research and Forecasting Chemistry model suggested that residential emission was the largest source of BC. Snow, Ice, and Aerosol Radiative modelling showed that the average contribution of BC and MD to snow albedo reduction was 17 and 3%, respectively. RF caused by BC significantly exceeded RF caused by MD. In different scenarios, changes in snow cover duration (SCD) caused by BC and MD decreased by 1.36 +/- 0.61 to 6.12 +/- 3.38 d. Compared with MD, BC was the main dominant factor in reducing snow albedo and SCD across NX.